Systemic effects of hypophosphatasia characterization of two novel variants in the ALPL gene - Martínez-Heredia, Luis; Muñoz-Torres, Manuel; Sanabria-de la Torre, Raquel; Jiménez-Ortas, Ángela; Andújar-Vera, Francisco; González-Cejudo, Trinidad; Contreras-Bolívar, Victoria; González-Salvatierra, Sheila; Gómez-Vida, José María; García-Fontana, Cristina; García-Fontana, Beatriz (Frontiers in Endocrinology, 2024)
Introduction Hypophosphatasia (HPP) is an inborn metabolic error caused by mutations in the ALPL gene encoding tissue non-specific alkaline phosphatase (TNSALP) and leading to decreased alkaline phosphatase (ALP) activity. Although the main characteristic of this disease is bone involvement, it presents a great genetic and clinical variability, which makes it a systemic disease. Methods Patients were recruited based on biochemical assessments. Diagnosis was made by measuring serum ALP and pyridoxal 5-phosphate levels and finally by Sanger sequencing of the ALPL gene from peripheral blood mononuclear cells. Characterization of the new variants was performed by transfection of the variants into HEK293T cells, where ALP activity and cellular localization were measured by flow cytometry. The dominant negative effect was analyzed by co-transfection of each variant with the wild-type gene, measuring ALP activity and analyzing cellular localization by flow cytometry. Results Two previously undescribed variants were found in the ALPL gene: leucine 6 to serine missense mutation (c.17T>C, L6S) affecting the signal peptide and threonine 167 deletion (c.498_500delCAC, T167del) affecting the vicinity of the active site. These mutations lead mainly to non-pathognomonic symptoms of HPP. Structural prediction and modeling tools indicated the affected residues as critical residues with important roles in protein structure and function. In vitro results demonstrated low TNSALP activity and a dominant negative effect in both mutations. The results of the characterization of these variants suggest that the pleiotropic role of TNSALP could be involved in the systemic effects observed in these patients highlighting digestive and autoimmune disorders associated with TNSALP dysfunction. Conclusions The two new mutations have been classified as pathogenic. At the clinical level, this study suggests that both mutations not only lead to pathognomonic symptoms of the disease, but may also play a role at the systemic level.